THE INFLUENCE OF TEACHER MANAGEMENT AND LEARNING RESOURCES ON STUDENT LEARNING OUTCOMES - Sahabuddin, Sriwahyuni; Yaumi, Muhammad; Hafid, Erwin (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This article discusses about the influence of teacher management and learning resource on student learning outcomes at State Senior High Schools in West Sinjai District, Sinjai Regency. This study uses a type of field research with a quantitative approach. The population in this study found 51 teachers and 436 students. The sample was determined randomly as many as 65 students and 51 teachers who were taken all fairly small. The data collection method used was a questionnaire and the results were analyzed using inferential statistical analysis with the help of SPSS. The results of the study prove that: 1) educator management has an effect on student learning outcomes with the regression equation Y= 55,437+0,353X; 2) learning resources management has an effect on student learning outcomes with the regression equation Y= 46,209+0,617X; and 3) teacher management and learning resources have a simultaneous effect on student learning outcomes and the level of influence is 25.1%. Therefore, the learning outcomes of students at State Senior High Schools in West Sinjai District can be determined by the good or bad of the teacher management and learning resources carried out.